Validitas Perangkat Pembelajaran Sains Model Proyek Berbantuan Augmented Reality Untuk Meningkatkan Literasi dan Kemampuan Berpikir Kreatif Peserta Didik - Naf'atuzzahrah Naf'atuzzahrah; Gito Hadiprayitno; Ahmad Harjono (Postgraduate, University of Mataram, 2024)
The development of project model science learning tools assisted by augmented reality has been carried out to improve students' literacy and creative thinking abilities. This development research aims to produce a valid product and describe the results of the validation of the learning device so that it is suitable for use in the learning process. This type of research is research and development with 4D model design which consists of the definition, design, development and dissemination stages. Validation of learning tools was carried out by three competent expert validators at Mataram University. The development of augmented reality-assisted project model science learning tools developed consists of a syllabus, lesson plans, teaching materials, LKPD, augmented reality media as well as scientific literacy test instruments and creative thinking ability test instruments. The results of the research show that the project model science learning tools assisted by augmented reality have very valid and reliable criteria so that they are suitable for use in the science learning process in schools to improve students' scientific literacy and creative thinking abilities.